Strategies of Teams in Soccerbots - R. Geetha Ramani; R. Subramanian; M. Sindurathy (International Journal of Advanced Robotic Systems, 2008)
TeamBots was designed and developed by Tucker Balch at Carnegie Mellon University, as development and testing environment for studying collaborative robot behaviour. This paper presents the strategies behind all the robot soccer teams available in the Teambots (soccerbot) package. The performances of the various soccer teams were analysed. This paper will aid the researchers to develop the soccer team with best strategies.